Patent Trolls: Evidence from Targeted Firms - Cohen, Lauren; Gurun, Umit G.; Kominers, Scott Duke (Management Science, 2019)
We provide the first large-sample evidence on the behavior and impact of nonpracticing entities (NPEs) in the intellectual property space. We find that, on average, NPEs appear to behave as opportunistic “patent trolls.” NPEs sue cash-rich firms and target cash in business segments unrelated to alleged infringement at essentially the same frequency as they target cash in segments related to alleged infringement. By contrast, cash is neither a key driver of intellectual property lawsuits by practicing entities (e.g., IBM and Intel) nor of any other type of litigation against firms. We find further suggestive evidence of NPE opportunism: targeting of firms that have reduced ability to defend themselves, repeated assertions of lower-quality patents, increased assertion activity nearing patent expiration, and forum shopping. We find, moreover, that NPE litigation has a real negative impact on innovation at targeted firms: firms substantially reduce their innovative activity after settling with NPEs (or losing to them in court). Meanwhile, we neither find any markers of significant NPE pass-through to end innovators, nor of a positive impact of NPEs on innovation in the industries in which they are most prevalent. This paper was accepted by Tyler Shumway, finance.